Pregnancy rate and litter size of English Bulldog bitches inseminated with fresh semen - Moya, Carla; Sanchez Hernandes, Bruna Muniz; ., Flávio Camargo Leme; ., Annelise Carla Camplesi (Pubvet, 2021)
The present study aimed to evaluate the estrus cycle of Bulldog bitches using vaginal cytology, and to inseminate these with fresh semen, leading to the determination of pregnancy rate and the size of the litter. Sixteen (16) English Bulldog breed bitches were used, all with good reproductive history and proved fertility, age ranging from 1.5 to 6 years. Associated with the proestrus detection (external signs: vulva edema and a blood-stained discharge) was performed the vaginal cytology in order to determine the estrus moment, as well was observed the female behavior of male acceptance. The artificial inseminations (AI) started when the vaginal cytology showed 90% of superficial cells, then repeated every 48h until the vaginal cytology change to diestrus (increasing the nucleated cell counting) and/or the bitch stop to accept the dog mating. To perform the semen collection were used the digital manipulation, all male breeders undergo to a previous seminal examination being select for use only ejaculates with more than 70% of total motility, vigor 3 and, at least, 200x106 of spermatozoa. The AI was performed using all the collected ejaculate. The gestation confirmation was made by transabdominal ultrasonography between 25 and 30 days after the last AI, the ultrasonographic evaluation after that was carried out periodically in order to determine the best moment to execute the c-section. The vaginal cytology evaluation, associated with the compartmental changes in the bitch was efficient to detect the estrus onset in 100% of the bitches. Get pregnant 14 of the 16 bitches inseminated (87.5%). The litters had a mean number of 5.6 puppies, of those 53.16% (42/79) were male and 46.84% (37/79) were female. The AI with fresh semen associated with vaginal cytology provided good fertility results and size of litters compatible in English Bulldog under these experimental conditions.